2007
DOI: 10.1093/sw/52.1.71
|View full text |Cite
|
Sign up to set email alerts
|

America's Changing Attitudes toward Homosexuality, Civil Unions, and Same-Gender Marriage: 1977-2004

Abstract: On May 17, 2004, Massachusetts became the first state to legalize same-gender marriage. From California to Missouri, nearly all states now face legislative challenges to the once firmly entrenched notion that marriage can only exist between a man and a woman. Public opinion polls conducted from 1977 to 2004 found that Americans' attitudes toward gay men and lesbians and marriages or civil unions for same-gender couples have evolved. Opposition persists, however. The most recent data indicate support for some l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 0 publications
0
77
0
Order By: Relevance
“…Policy debates about same-sex marriage span both federal and state levels of government and have considerable implications for gay and lesbian couples (Woodford 2010). Pollsters and academic researchers have investigated opinions about same-sex marriage since the 1990s (Avery et al 2007;Brewer and Wilcox 2005). Studies have identified covariates of opinions toward same-sex marriage; however, research has not investigated the covariates of reporting "neutral" or "undecided."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Policy debates about same-sex marriage span both federal and state levels of government and have considerable implications for gay and lesbian couples (Woodford 2010). Pollsters and academic researchers have investigated opinions about same-sex marriage since the 1990s (Avery et al 2007;Brewer and Wilcox 2005). Studies have identified covariates of opinions toward same-sex marriage; however, research has not investigated the covariates of reporting "neutral" or "undecided."…”
mentioning
confidence: 99%
“…For example, 65% of the respondents in the 2010 American Freshman Survey supported same-sex marriage (Pryor et al 2010); whereas a recent Gallop Poll found 53% of Americans favor this policy option (Newport 2011). Additionally, college students elect a neutral or unsure response at much higher rates (between 15% and 21%; Cluse-Tolar et al 2005;Jenkins et al 2007;Lannutti and Lachlan 2008;Swank and Raiz 2010) than the general public (<5%; see Avery et al 2007;Brewer and Wilcox 2005), thereby indicating that college students, and younger generations more generally, may also be a particularly persuadable demographic group.…”
mentioning
confidence: 99%
“…Globally, attitudes towards LGBT individuals and same-sex relationships have become increasingly more accepting, although active opposition against equal rights for these individuals still exist (Camilleri and Ryan 2006;Ellis 2009;Avery, Chase, Johansson, Litvak, Montero and Wydra 2007). Research, however, indicates that acceptance of same-sex relationships varies across social contexts, e.g., countries and faculties.…”
Section: Couples' Experiences On University Campusesmentioning
confidence: 99%
“…Given that public attitudes play a key role in determining legislation, homophobia has historically been enshrined in U.S. public policy (Burstein 1998). Yet researching these attitudes is complex, as they can pertain to: sexual acts (Keleher and Smith 2012); individuals and sexual identities (Seidman 2002); personal morality (Loftus 2001); and civil rights (Avery et al 2007). There also exists variance in attitudes pertaining to gay, lesbian, bisexual or transgender identities (Worthen 2013), and it is thus important to 4 examine attitudes toward these groups individually, as well as investigating their intersectionality with other modes of oppression (Crenshaw 1991).…”
Section: Defining Homophobiamentioning
confidence: 99%